Optimizing Social Media Engagement To Enhance Purchase Decisions: Evidence From Tiktok Consumers Of Monggoo Mebel - Amar Mustofa; Ali Ali, M. Rifqy Roosdhani (STIE AMKOP, 2026)
This study examines the effects of influencer attractiveness, limited offer, and perceived enjoyment on purchase decisions, with social media engagement as a mediating variable, among TikTok consumers of Monggoo Mebel, an Indonesian furniture brand. The research integrates the Stimulus – Organism - Response framework, Social Media Engagement Theory, and the Theory of Planned Behavior, and adopts an explanatory quantitative design. Data were collected in 2026 through a 1–10 Likert-scale questionnaire from 264 respondents selected by purposive sampling, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The measurement model showed strong validity and reliability, and all ten hypothesized relationships were supported. Limited offer was the strongest driver of purchase decision, followed by social media engagement and perceived enjoyment, and engagement significantly mediated the effects of all three stimuli. Influencer attractiveness raised purchase decision directly yet reduced engagement, forming a competitive indirect path. The model explained 77.7% of the variance in purchase decision. These findings extend engagement-mediation logic to high-involvement durable goods and help furniture SMEs prioritize their TikTok content strategies. Keywords: influencer attractiveness; limited offer; perceived enjoyment; social media engagement; purchase decision.